The Impact of Liberal Feminism Movement in A Promptbook He and She - Sunarti Desrieny Tambunan; Ratna Safitri (Prodi Sastra Inggris UKI, 2022)
Liberal feminism is a universal approach in which women and men are equal in basic rights such as education, work, financial security, voting and many more. This research aims to find out the impact of emancipation movement in a promptbook entitled He and She play using Tong and Botts’ theory. The method used in this research is a descriptive qualitative method. The result shows that most of the characters in the promptbook accept the movement, except Keith, Ruth’s boyfriend, who thinks women in his era act like superiors because of the movement. He does not accept it by showing that his girlfriend cannot have a higher position than him. She cannot work and just stay at home after they get married. At the end, he will only cut his girlfriend’s half-life. This movement can give good or bad impact for the society or surroundings, especially the men. For those who are old-fashioned thinking, this can be a threat.